Status Paritas dengan Tingkat Kecemasan Pada Ibu Pre Operasi Sectio Caesarea - Ni Made Dewi Susanti; Risma Putri Utama (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction; Pregnancy is a vulnerable period of risk of psychological disorders for a pregnant woman; one of these disorders is anxiety. Parity is a history of childbirth with the number of pregnancies as a physiological state that can be followed by pathological processes that can threaten the state of the mother and fetus. Ideally, the parity of a pregnant woman is 2 3 with a delivery distance of 3-4 years. Purpose; Knowing the relationship between the parity status of pregnant women with the level of anxiety of preoperative Sectio Caesarea mothers. Method; This study used a correlation descriptive design with a cross-sectional approach and purposive sampling technique performed on 34 pregnant women with preoperative Sectio Caesarea. The questionnaire used was the Hamilton Rating scale for Anxiety (HRS-A). Results; Based on the results of the analysis that has been carried out using the chi-square test obtained with a p-value of 0.004. Conclusion; There is a significant association between parity and anxiety status in preoperative mothers of section Caesarea. Anxiety preoperative mother Sectio Caesarea experiences mild anxiety.